Business Opportunity : Projek Outdoor / Aisyah Harun - Harun, Aisyah (2021)
I need to perform a business opportunity in order to fulfill my individual task for Fundamental of Entrepreneurship (ENT300), which is a business opportunity focused on Business Model Canvas. .Business that I chose is Projek Outdoor which is has potential to grow in business. This service is enjoyable and fun, so people can have a quality time with family. The main services of Projek Outdoor is White water rafting which is located in Ulu Slim. At Ulu Slim, there is no business like this so it gave a big opportunities to be the first person to produce this service. I got more information to write this task through website and Google.